Maritime moving target localization method based on improved differential evolution with GNSS-based passive multistatic radar - HE Zhenyu; MAO Yi; YANG Yang; CHEN Wu (Tongxin xuebao)
A maritime moving target localization method based on improved differential evolution with GNSS-based passive multistatic radar was proposed by using the multi-satellite characteristics of global navigation satellite system based passive radar systems. First, the long integration technique was exploited by multiple bistatic geometry configurations to focus target energy in the rangee-Doppler domains, Then, the focused target energy was projected into the Cartesian plane for joint detection and localization. To enhance the efficiency of the projection processing, an improved differential evolution was put forward, which could ensure algorithm convergence and maintain population diversity by the co-evolution strategy of superior and inferior populations. The simulated and real experimental results demonstrate that the proposed method can provide positioning and velocity estimation accuracies similar to the existing algorithm, but with a significantly decreased computational time.